Pengaruh Proses Pembuatan yang Saniter Terhadap Masa Simpan Jamu Gendong di Kelurahan Kricak, Tegalrejo, Yogyakarta, Tahun 2014 - Neni Purwandari; Mohammad Mirza Fauzie; Muryoto Muryoto (Poltekkes Kemenkes Yogyakarta, 2014)
“Gendong” herb is tradisional medicine in the form of liquid which is circulated without indication. Undirectly, the consumption of this herb is one possible factor that affect diarrhoea incidence among people if sold in poor condition as results of the production that unfulfilling the sanitation standard. The purpose of this study was to know the difference of storage period of five types of ‘gendong herb’; i.e. kunyit asam, beras kencur, pahitan, uyup-uyup dan cabe puyang; produced by herb makers who followed good sanitation requirements and those who did not, in Kricak, Te-galrejo, Yogyakarta City. The study employed Extended Storage Studies method to determine the storage period of the herb types by using organoleptic observation, which consist of odor, color, taste and viscosity. The results of analysis using independent t-test, at ? = 0,005, obtained p-value of 0,001, which means that the storage periods of the herbs yielded from the two groups was significantly different.